From Kanyādāna to Consent: The Making of Marriageable Age in Hindu Law (Dhaka University Law Journal, 2026)
This article reconstructs how “marriageable age” in Hindu law was made across doctrinal, institutional, and evidentiary registers. It traces the shift from a guardianship- centred kanyādāna framework, where puberty and household competence acted as proxies, to a modern regime organised around consent and statutory majority. Colonial change proved pivotal: the fabrication of “Anglo-Hindu law”, the move from paṇḍit-assisted adjudication to High Court precedent, and proof rules under the Indian Evidence Act 1872 together made age a justiciable fact. Criminal-law overlays, including the marital rape exception and the Age of Consent Acts 1891 and 1925, were stress-tested in litigation and fed into the civil age conditions of the Sarda/Child Marriage Restraint Act. Contemporary trajectories in India, Nepal, Pakistan, Sri Lanka, and Bangladesh expose the structural effects of registration design and “special-circumstances” waivers. The article concludes with a proportionate reform template and a research agenda grounded in registries, court files, and enforcement records.Dhaka University Law Journal, 2025, 36(2), 23-52